Nashaly10
Nashaly10
02-10-2020
Mathematics
contestada
Solve for f: f/3 - 4 = 6
Respuesta :
xcfgvhbjnkml
xcfgvhbjnkml
02-10-2020
Answer:
f = 22
Step-by-step explanation:
f/3 - 4 = 6
3 x f/3 -4 = 6 x 3
f - 4 = 18
f - 4 +4 = 18 + 4
f = 22
Answer Link
VER TODAS LAS RESPUESTAS ( 36+ )
Otras preguntas
Given a=8, b=7 and c =6, use the law of cosines to solve the triangle for the value of C. Round answer two decimal. a. 80.44 b. 46.57 c. 57.91 d. 75.52
Drugs of abuse trigger the release of dopamine within our brain. True or False
simplify or reduce the answer to 1/4+2/7+1/2
Consider the equation (x^m)=(x^13)^5 x(x^-8)^-5 The value of m is A. 15 B. 28 C. 35 D. 70
Paid vacations and sick leave are
The position of an object is given by the equation x = 4.0t2 - 2.0 t - 4.5where x is in meters and t is in seconds. What is the instantaneous acceleration, velo
2. Let f(x) = -2x - 7 and g(x) = -4x + 6. Find(gof)(-5).
What are three reasons why the glass-steagall act became less and less effective?
find the quotient of 226.84 round your answer to the nearest tenth
What is the slope and y-intercept of the equation 3(y − 2) + 6(x + 1) − 2 = 0? A. slope = -2, y-intercept = B. slope = 2, y-intercept = C. slope = -2, y-in